Determinan Audit Judgment Auditor Di Masa Pandemi Covid-19 - Agustiawan Agustiawan; Rama Gita Suci; Rahmatul Fauziah (Akuntansi & Ekonomika, 2021)
The purpose of this study was to partially examine the effect of compliance pressure, time budget pressure, and auditor experience on audit assessments during the Covid-19 Pandemic. Sampling in this study using non-probability sampling with saturated samples. Respondents in this week's study were auditors of new public accounting firms. This research method is a quantitative method. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that compliance pressure, time budget pressure, and auditor experience each have an effect on audit assessments during the Covid-19 pandemic.